Coronavirus disease 2019-associated rapidly progressive organizing pneumonia with fibrotic feature: Two case reports. Issue 35 (28th August 2020) - Okamori, Satoshi; Lee, Ho; Kondo, Yasushi; Akiyama, Yuto; Kabata, Hiroki; Kaneko, Yuko; Ishii, Makoto; Hasegawa, Naoki; Fukunaga, Koichi
Abstract: Introduction: Pneumonia is one of the most important characteristics of coronavirus disease 2019 (COVID-19) and imaging findings of COVID-19 pneumonia are diverse and change over disease course. However, the detailed clinical course of organizing pneumonia (OP) caused by COVID-19 has not been clarified. Patient concerns: A 60-year-old man and a 61-year-old woman diagnosed with mild COVID-19 were admitted to our hospital. Their respiratory symptoms were deteriorating even after initiating treatment with antiviral drugs. Diagnosis: Chest X-rays and computed tomography scan showed a rapid progression of linear consolidation with reversed halo sign, distributed in subpleural and peri-bronchial regions. They also presented with pulmonary fibrosis findings, including traction bronchiectasis and marked lung volume reduction. They were diagnosed with rapidly progressing OP. Interventions: They were treated with systemic corticosteroids. Outcomes: The patients' imaging findings and respiratory conditions improved rapidly without any adverse effects. Conclusion: Physicians should carefully monitor patients with COVID-19, as they can develop rapidly progressive and fibrotic OP, which respond to corticosteroids.